Resource allocation for a switched multibeam OFDMA system - Simon, Dwight David M. (2007)
Multicarrier and multichannel transmission schemes have been widely adopted in broadband wireless communications systems due to its suitability for multiuser access and parallel transmission of their corresponding bit streams resulting in achievement of high data rates. OFDMA allocates subcarriers to the bit streams of multiple users with the two-old objective of providing the users' data rate requirements and simultaneously minimize overall transmit power at the base station. A Switched Multibeam OFDMA system is a robust and simple, multiuser OFDM system characterized by a finite number of fixed beams, predefined directional beam patterns and reduced beamwidths. The performance advantages are extended coverage area with reduced interference, allowing the reuse of subcarriers (frequency) in multiple beams. Reuse of subcarriers results in a significant increase in spectral efficiency leading to corresponding increase in overall system capability. The proposed MULTIBEAM algorithm for a 3x40 degree beam 120 degree sector switched multibeam OFDMA system achieved an average capacity of 13.62 bps/Hz to 14.78 bps/Hz or an increase of 47% to 60% versus the omnisector-based LINEAR algorithm. This result is achieved with a reuse factor of 75%, i.e. Reuse of 75% of the higher quality subcarriers in the two edge beams. By maximizing the use of best quality subcarriers in the two edge beams, system capacity is increased. The reuse factor may be adjusted to best serve the traffic requirements in various conditions.
"April 2007."
Thesis (Ph.D. Electrical and Electronics Engineering)--University of the Philippines Diliman.
Keywords: Wireless communication systems; Telecommunication systems; Resource allocation; OFDMA system; Orthogonal Frequency Division Multiple Access